The Role of Job Demands and Job Resources in Mediating the Influence of Leadership Practices on Work Engagement, and Their Impact on the Performance of Police Personnel at the Southeast Sulawesi Regional Police (Architecture Image Studies, 2025)
This study aims to analyze the influence of leadership practices, job demands, and job resources on work engagement and their impact on the performance of Indonesian National Police personnel at the Southeast Sulawesi Regional Police, including testing the mediating role of job demands, job resources, and work engagement in the developed relationship model. The study population consisted of 2,211 personnel, with a sample of 187 respondents determined using the Slovin formula at a precision level of 7 percent. The research approach used a quantitative method with Partial Least Squares (PLS) analysis to test direct and mediating relationships between variables. The results showed that leadership practices had a positive and significant effect on job demands, job resources, work engagement, and personnel performance. In addition, job demands were proven to have a positive and significant effect on work engagement, while job resources had no significant effect. Work engagement had a positive and significant effect on personnel performance. The mediation analysis revealed that job demands acted as a full mediator in the relationship between leadership practices and work engagement, while job resources did not act as a mediator. Meanwhile, work engagement acted as a partial mediator in the relationship between leadership practices and personnel performance. The findings of this study extend the JD-R model by presenting performance variables as the primary output and highlighting the importance of leadership practices in shaping adaptive work demands and work engagement, which impact personnel performance. The theoretical and practical implications of this study can serve as a reference for the Southeast Sulawesi Regional Police (Polda Sultra) in strengthening leadership strategies and human resource management to improve organizational performance.